Zenali Iteration Method For Approximating Fixed Point of A Î´ZA - Quasi Contractive mappings - Maibed, Zena Hussein; Thajil, Ali Qasem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
This article will introduce a new iteration method called the zenali iteration method for the approximation of fixed points. We show that our iteration process is faster than the current leading iterations  like Mann, Ishikawa, oor, D- iterations, and *-  iteration for new contraction mappings called  quasi contraction mappings. And we  proved that all these iterations (Mann, Ishikawa, oor, D- iterations and *-  iteration) equivalent to approximate fixed points of  quasi contraction. We support our analytic proof by a numerical example, data dependence result for contraction mappings type  by employing zenali iteration also discussed.